2013
DOI: 10.1111/1754-9485.12048
|View full text |Cite
|
Sign up to set email alerts
|

Integral dose delivered to normal brain with conventional intensity‐modulated radiotherapy (IMRT) and helical tomotherapy IMRT during partial brain radiotherapy for high‐grade gliomas with and without selective sparing of the hippocampus, limbic circuit and neural stem cell compartment

Abstract: In the setting of PBRT for high-grade gliomas, IMRT reduces IDbrain compared with HT with or without selective SPA of contralateral hippocampus, limbic circuit and NSC, and the use of selective SPA reduces IDbrain compared with STD PBRT delivered with either traditional IMRT or HT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 35 publications
(55 reference statements)
0
14
0
Order By: Relevance
“…Our dosimetric results for VMAT planning also showed a trend toward dose reduction when compared to 3D-CRT in contralateral OAR and the infratentorial brain. However, for future multiplearc treatments, non-coplanar VMAT [43,44] might be an excellent study objective to provide further improvements in OAR sparing in HGG.…”
Section: Discussionmentioning
confidence: 99%
“…Our dosimetric results for VMAT planning also showed a trend toward dose reduction when compared to 3D-CRT in contralateral OAR and the infratentorial brain. However, for future multiplearc treatments, non-coplanar VMAT [43,44] might be an excellent study objective to provide further improvements in OAR sparing in HGG.…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to minimize dose in hippocampus, there is a risk of overtreatment of other parts of the brain and surrounding structures with increased risk of induced secondary malignancies. To assess this potential disadvantage of helical tomotherapy, one study measured integral doses in uninvolved brain regions of HGG patients for both conventional IMRT and helical tomotherapy techniques [57]. The results proved reduction of brain integral dose in average by 23% after IMRT compared with tomotherapy in all tested treatment plans.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Also, not little evidence supports that impaired hippocampal neurogenesis caused by radiation-induced damage [10][11][12][13] should be strongly associated with NCF impairment. [9,14] Furthermore, several studies showed that isodose distribution in the hippocampus is closely related to NCFs in patients with primary brain tumors [15][16][17] or in those with nasopharyngeal carcinoma. [14] Consequently, it is hypothesized that conformal hippocampal avoidance during the course of WBRT (HA-WBRT) might lead to significant preservation in terms of cognitive function.…”
Section: What This Study Adds To the Fieldmentioning
confidence: 99%